Preclinical Study of n-Hexane Extract of Kapul Fruit (Baccaurea macrocarpa) as an Anti-Inflammatory - Rizki, Muhammad Ikhwan; Rahmatullah, Satrio Wibowo; Izma, Hayatun; Isnani, Nazhipah; Ramadhani , Syahrizal (Universitas Borneo Lestari, 2025)
Plants of the genus Baccaurea have long been traditionally used in folk medicine. Previous studies reported that the n-hexane extract of kapul fruit (Baccaurea macrocarpa) exhibited extreme antioxidant activity with an IC₅₀ value of 33.11 ppm. However, its potential anti-inflammatory activity has not been extensively investigated. The results demonstrated that all three doses of the n-hexane extract exhibited anti-inflammatory activity, as indicated by a reduction in edema volume. Among the tested doses, 600 mg/kg BW was the most effective ini decreasing edema volume. Statistical analysis using one-way ANOVA showed a significance value of 0.000, confirming a significant difference among the five treatment groups. Furthermore, post hoc analysis indicated that dose III did not differ significantly from the positive control but showed a significant difference compared to the negative control. Conversely, doses I and II exhibited significant differences when compared to both the positive and negative controls. These findings suggest that the n-hexane extract of B. macrocarpa fruit possesses anti-inflammatory activity, with the 600 mg/kg BW dose demonstrating the most potent effect, comparable to that of diclofenac sodium